The Forest Carbon Partnership Facility - Independent Evaluation Group (Washington, DC: World Bank Group, 2015)
This is the Global Program Review (GPR) of the Forest Carbon Partnership Facility (FCPF). The objectives of the Facility are: (a) to assist eligible Reduced Emissions from Deforestation and Forest Degradation (REDD) countries in their efforts to achieve emission reductions from deforestation and/or forest degradation by providing them with financial and technical assistance in building their capacity to benefit from possible future systems of positive incentives for REDD; (b) to pilot a performance-based payment system for emission reductions generated from REDD activities, with a view to ensuring equitable benefit sharing and promoting future, large-scale positive incentives for REDD; (c) to test ways to sustain or enhance livelihoods of local communities and to conserve biodiversity; and (d) to disseminate broadly the knowledge gained in the development of the Facility and implementation of readiness preparation proposals and emission reduction programs. This review concludes that that the FCPF has been an innovative program that has added significant value at the global level in defining the modalities of REDD+ and has produced a roadmap for countries to achieve REDD+ readiness. The FCPF has been willing to take risks and pioneer new ways of doing business. It has created a space for inclusive and transparent debate among donors, forested developing countries, civil society, indigenous peoples' groups and forest-dependent communities around REDD+. FCPF management could enhance its effectiveness by revisiting its supervision formulas, taking advantage of internal World Bank reforms relating to micro and small grants, and by developing a programmatic results framework that is more reflective of the technical assistance and financial services that it provides.